TERAPI AKTIVITAS KELOMPOK (TAK) TERAPI KOGNITIF : SENAM OTAK TERHADAP PENINGKATAN FUNGSI KOGNITIF PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA BUDI MULIA 2 WISMA MANGGA - Alfika Safitri; Annisa Shiratul Khivari; Ardina Nurfadillah Febianah; Rizma Aulia Putri; Andre Wirakusuma; Soniatun Nisya; Aldini Aulia; Tiara Chandra Kirana; Nyimas Patimiyah; Anisa Fitriana; Dina Meliyani; Dian Purnamasari (Yayasan Nusantara Hasana Berdikari, 2023)
Background: Elderly is someone who is more than 60 years old based on Law Number 13 of 1998 concerning Elderly Welfare (Ministry of Health, 2016). According to WHO, the elderly are divided into three categories, namely, old age (60-70 years), old age (75-89 years and very old age (> 90 years). An elderly person will experience physical and psychological decline. Psychological decline in the elderly will cause changes in character and behavior that can lead to problems in the elderly. Problems that are often found in the elderly are memory loss, senility, depression, irritability, offense, and suspicion. Brain gym therapy is one of the motion therapies which is considered as one of the a way to treat individual mental illness. exercise therapy is given to elderly patients as an effort to improve the ability of patients so that they are able to live more independently and be able to carry out daily activities. Objective: After doing Group Activity Therapy (TAK), brain exercise is expected to improve the memory and concentration of the elderly. The elderly can respond to the stimulus provided by the nurse, namely music. Elderly can express their feelings in the form of pleasant experiences. Research Design: using lecture and question and answer methods as well as carrying out brain gym activities simultaneously. The results of the study: this brain gymnastics participants can enjoy the activities they do so that brain gymnastics can reduce boredom and can assess gross motor skills, fine motor skills, language, cognitive and socialization according to their age level, the purpose of this brain exercise is to slow down senility, relieve stress, improve concentration, make emotions calmer. It is hoped that the elderly can train their sensory, motor and cognitive skills with brain exercise therapy.